To respond or not to respond, the recurring question in plant mechanosensitivity - Leblanc-Fournier, Nathalie; Martin, Ludovic; Lenne, Catherine; Decourteix, Mélanie (Frontiers in Plant Science, 2014)
In nature, terrestrial plants experience many kinds of external mechanical stimulation and respond by triggering a network of signaling events to acclimate their growth and development. Some environmental cues, especially wind, recur on time scales varying from seconds to days. Plants thus have to adapt their sensitivity to such stimulations to avoid constitutive activation of stress responses. The study of plant mechanosensing has been attracting more interest in the last two decades, but plant responses to repetitive mechanical stimulation have yet to be described in detail. In this mini review, alongside classic experiments we survey recent descriptions of the kinetics of plant responses to recurrent stimulation. The ability of plants to modulate their responses to recurrent stimulation at the molecular, cellular, or organ scale is also relevant to other abiotic stimuli. It is possible that plants reduce their responsiveness to environmental signals as a function of their recurrence, recovering full sensitivity several days later. Finally, putative mechanisms underlying mechanosensing regulation are discussed.